2019
DOI: 10.5137/1019-5149.jtn.25018-18.2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of empirical antibiotic treatment in culture-negative pyogenic vertebral osteomyelitis

Abstract: AIM: To investigate the efficacy of empirical antibiotic treatment in culture-negative pyogenic vertebral osteomyelitis (PVO) cases. MATERIAL and METHODS: The records of patients with culture-negative PVO who were treated at infectious disease and neurosurgery outpatient clinics in the past four years were examined retrospectively. The control group comprised healthy subjects with similar age, gender, and body mass index but without pathology. In the statistical evaluation of the obtained data, the comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In human medicine, suspected infectious diseases with negative tissue culture, such as spondylodiscitis, vertebral osteomyelitis, sepsis, endocarditis and periprosthetic joint infections, have been widely reported ( 30 34 ). In our study, 10 out of 12 dogs in which discospondylitis was treated surgically, had an IVD sample taken.…”
Section: Discussionmentioning
confidence: 99%
“…In human medicine, suspected infectious diseases with negative tissue culture, such as spondylodiscitis, vertebral osteomyelitis, sepsis, endocarditis and periprosthetic joint infections, have been widely reported ( 30 34 ). In our study, 10 out of 12 dogs in which discospondylitis was treated surgically, had an IVD sample taken.…”
Section: Discussionmentioning
confidence: 99%
“…There is no clear treatment guideline for SEA with negative bacterial culture, and such treatment mainly depends on empirical medication. 23 With the increase of culture-negative patients in clinical practice, 24 it is more and more important to improve the understanding and clinical treatment of negative SEA culture. The vast majority of our cases (in the literature and in our present study) are caused by Gram-positive cocci, mainly S. aureus (67%).…”
Section: Figurementioning
confidence: 99%
“…Studies have reported the clinical features and results of culture-negative purulent spondylitis [7]. However, the treatment of patients with culture-negative purulent spondylitis mainly relies on empirical medication [8], and there is no established standard Treatment principles. It is increasingly important to improve the understanding and clinical treatment of culture-negative purulent spondylitis.…”
Section: Introductionmentioning
confidence: 99%